Ibogaine Detoxification Transitions Opioid and Cocaine Abusers Between Dependence and Abstinence: Clinical Observations and Treatment Outcomes - Mash, Deborah C.; Duque, Linda; Page, Bryan; Allen-Ferdinand, Kathleen (Frontiers in Pharmacology, 2018)
Ibogaine may be effective for transitioning opioid and cocaine dependent individuals to sobriety. American and European self-help groups provided public testimonials that ibogaine alleviated drug craving and opioid withdrawal symptoms after only a single dose administration. Preclinical studies in animal models of addiction have provided proof-of-concept evidence in support of these claims. However, the purported therapeutic benefits of ibogaine are based anecdotal reports from a small series of case reports that used retrospective recruitment procedures. We reviewed clinical results from an open label case series (N=191) of human volunteers seeking to detoxify from opioids or cocaine with medical monitoring during inpatient treatment. Whole blood was assayed to obtain pharmacokinetic measures to determine the metabolism and clearance of ibogaine. Clinical safety data and adverse events (AEs) were studied in male and female subjects. There was no significant toxicity observed over a range of oral ibogaine doses that were shown to be effective for blocking opioid withdrawal symptoms in this study. We used multi-dimensional craving questionnaires during inpatient detoxification to test if ibogaine was effective in diminishing heroin and cocaine cravings. Participants also completed standardized questionnaires about their health and mood before and after ibogaine treatment, and at program discharge. One-month follow-up data were reviewed where available to determine if ibogaine’s effects on drug craving would persist outside of a controlled inpatient environment. We report here that ibogaine therapy administered in a safe dose range diminishes opioid withdrawal symptoms and reduces drug cravings. Pharmacological treatments for opioid dependence include detoxification, narcotic antagonists and long-term opioid maintenance therapy. Our results support product development of single oral dose administration of ibogaine for the treatment of opioid withdrawal during medically supervised detoxification to transition drug dependent individuals to abstinence.